Festivals de cinéma dans le monde arabe - Jean-Michel Frodon (Revue des Mondes Musulmans et de la Méditerranée)
While the two major “historical” film festivals in the Arab World - Cartago and Cairo -, have been declining, other film festivals have emerged in the area since 2000. Leading the way is Morocco, in spite of the contrast between the glamorous Marrakech festival and a swarm of minor events. In the Emirates, the large number of festivals reflects a self promotion strategy rather than a cultural development policy. As they compete between themselves, they become less attractive. In other countries, there is a feeling of dispersion due to a wide range of situations. Yet, the proliferation of festivals (around one hundred in the region) ends up creating a global effect, beyond individual goals, means and limits. Though enshrined in local or national roots, the festival phenomenon engenders on a wider scale generational, and financial networks, expertise procedure, interrelational process, and geographical thematic connections as well as connections between other arts and medias.